- KARAKTERISASI METALURGI SAMBUNGAN LAS SMAW PADA BAJA ST 37: ANALISIS STRUKTUR MIKRO DAN KEKERASAN PADA EDGE JOINT: - - Ananda Sylvano; Sigiet Haryo Pranoto; Anis Siti Nurrohkayati (JURNAL CRANKSHAFT, 2026)
This study investigates the relationship between microstructural changes and mechanical properties in an edge joint of ST 37 steel following Shielded Metal Arc Welding (SMAW) at 100 A using an E6013 electrode, without subsequent heat treatment. The analysis focuses on the Weld metal, Heat Affected Zone (HAZ), and Base metal through metallographic examination and Vickers hardness testing. The results indicate that variations in hardness values are strongly influenced by microstructural transformations induced by the thermal cycle during welding. The HAZ exhibits the highest hardness (172 HV), which correlates with an increase in the pearlite fraction to approximately 60% because of a relatively rapid cooling rate. This phase transformation leads to a harder microstructure, although it tends to be more brittle compared to the other regions. Meanwhile, Weld-metal records a hardness of 157 HV, and the Base metal shows 142 HV, reflecting differences in composition and thermal history across each zone. Overall, the average joint hardness of 157.33 HV demonstrates that despite significant microstructural modifications, the mechanical integrity of the welded joint remains acceptable and meets relevant standards.